Current Awareness Services and Information Dissemination in Universities -Western Uganda: A Case study of Ankole Western University. - Kanyamuhanga, Benjamin (Kabale University, 2024)
This research examines the use of Current Awareness Services (CAS) in information dissemination at Ankole Western University. The study aims to explore the different types of CAS employed within the institution, assess the challenges encountered during their implementation, and propose viable solutions to address these challenges. A mixed-methods approach was used, incorporating both qualitative and quantitative data collection tools such as interviews, questionnaires, and document analysis. The findings reveal a range of CAS types, including email alerts, bulletin boards, and social media platforms, as key tools for keeping users informed. However, the study highlights several challenges, including limited technological infrastructure, lack of user training, and low awareness among students and staff about the availability of CAS. Based on these findings, recommendations are provided, including improving technological support, increasing user training, and enhancing communication strategies to boost the effectiveness of CAS at the university. These solutions aim to optimize the dissemination of relevant and timely information to the university community.